2016
DOI: 10.11118/actaun201664051661
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Levels in Muscle Tissue of Six Wild Feathered Species

Abstract: The objective of this study was to determine and compare the levels of amino acids (AAs) in breast and thigh muscles of six species of feathered game of the same age. The experiment involved the following species: wild turkey (Meleagris gallopavo), guinea fowl (Numida meleagris), chukar partridge (Alectoris chucar), Japanese quail (Coturnix coturnix japonica), common pheasant (Phasianus colchicus) and grey partridge (Perdix perdix). The highest content of AAs was found in the chukar partridge (breast: 815.7 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Moreover, the same observation was reported by Aronal et al, (2012) who found that for domestic ducks the major non-EAA were glutamic, Aspartic, and Alanine. Furthermore, the results are in agreement with the results of Straková et al, (2016) for wild feathered species meats, the highest levels of non-EAA in both breast and thigh muscles were represented by glutamic and Aspartic. Moreover, for wild duck meat Khalifa and Nassar, (2001) found that glutamic, Aspartic, arginine and Alanine presented the highest concentration of non-EAA.…”
Section: Fig1 Graphical Abstractsupporting
confidence: 89%
“…Moreover, the same observation was reported by Aronal et al, (2012) who found that for domestic ducks the major non-EAA were glutamic, Aspartic, and Alanine. Furthermore, the results are in agreement with the results of Straková et al, (2016) for wild feathered species meats, the highest levels of non-EAA in both breast and thigh muscles were represented by glutamic and Aspartic. Moreover, for wild duck meat Khalifa and Nassar, (2001) found that glutamic, Aspartic, arginine and Alanine presented the highest concentration of non-EAA.…”
Section: Fig1 Graphical Abstractsupporting
confidence: 89%